The impact of non-ionizing electromagnetic radiation emitting devices on the male reproductive system - Sienkiewicz, Michał; Pawłowski, Bartosz; Kłusek, Magdalena; Zatłoka-Mazur, Dorota; Klimas, Filip; Rusiński, Kacper; Sienkiewicz, Bartłomiej (Quality in Sport, 2025)
With today’s technological advances, people spend more and more time using various devices that emit non-ionizing radiation (NIR), such as mobile phones, laptops or WiFi networks. Nowadays, the role of these devices in the human lifestyle seems to make exposure to NIR unavoidable. This exposure, especially when prolonged, has been reported as one of the possible lifestyle factors contributing to reduced fertility, especially in men. The aim of the study was to analyse the current state of knowledge on the impact of NIR emitted by modern devices on the functioning of the male reproductive system and to identify possible mechanisms behind it. The research method used was a literature review on the PubMed platform. A total number of 35 articles from years 2007-2024 were analysed. According to the scientific literature, exposure to NIR may affect spermatozoa through thermal and non-thermal mechanisms, the most important of which appears to be increased production of reactive oxygen species (ROS), which leads to oxidative stress and cellular damage in the reproductive system. NIR exposure can adversely affect semen parameters such as sperm motility, viability and concentration, alter hormonal mechanisms regulating reproduction and induce morphological changes in reproductive tissues. However, studies conducted in this context often provide inconsistent results, hence the exact effect of NIR on the male reproductive system remains unknown. Therefore, further research is needed to accurately determine the effects of NIR on male fertility and to provide appropriate health recommendations.